Alla scoperta dell’acqua! Unità didattica interdisciplinare realizzata in modalità laboratoriale - Marchini, Marianna; Cameran, Erica (Chimica nella Scuola, 2024)
This paper reports an interdisciplinary teaching unit design for a 4th grade of a primary school and tested in the outskirt of Bologna aimed to investigate three of the properties of water (surface tension, capillarity, and solvent power) by using the “hands-on, minds-on” approach of the 5Es instructional model. The three properties of water were investigated at both macro and sub-micro level. The experiments were designed to be performed autonomously by the students; two atomic theories were explored with multimedial teaching material to deepen the peculiar behavior of water molecule.